Friendship quality in 8 to 10 years old children who live in a public institution of Lima - Argumedo Bustinza, Doris (2006)
This research studies friendship relationships in institutionalized children according to friendship’s quality and reciprocity. The participants were 33 institutionalized children (boys and girls), whose age range was 8 to 10. The control group consisted of 41 noninstitutionalized children with similar characteristics. Results show that institutionalized children have less reciprocal friendships than non-institutionalized children. Institutionalized children give more support and share the ir intimate experienc es in their reciprocal friendships than non-institutionalized children. Moreover, friendship quality of non-reciprocal friendships in the institutionalized group is almost equivalent to reciprocal and non-reciprocal friendships in the non-institutionalized one. This evidence shows that the majority of institutionalized children establish friendship bonds with similar characteristics, as do other children of the same age range.